Preparation of a concentrated and resolubilized protein (CRP)I powder from mung bean protein isolate - Guerrero, Alfredo C.
This investigation aims to prepare from the mung bean (Phaseolus aureus, Roxb.) protein by production of the sotanghon industry, a low cost Concentrated and Resolubilized Protein (CRP) for use as skim milk extender. Under the condition of this experiment, optimum levels of mung bean protein and starch extraction were attained through a 3-stage extraction technique employing first, tap water, the 0.3% Na3Po4, and last tap water again as extractants. The mung bean grits were ground in a volume of extractant 5 times the weight of the grits in a colloid mill. the combined protein isolate recovered was dissolved in clear protection extract from the first extraction, and blended with the added butterfat and emulsifier to produce an emulsion. Using Molsin, a proteolyctic enzyme, the protein in the emulsion was degraded into peptide units. After thermal processing and homogenization, the emulsion was drum dried at 40 psig to produce CRP flakes. The resulting CRP flakes of 60 mesh finess, showed a protein content of about 48% (10% moisture) a fat content ranging from 10-11% and a Nitrogen Solubility Index (NSI) of 86-89%. The control of the following factors were found necessary in the preparation of CRP: (a) cooking temperature to destroy the anti-trypsin factors; (b) correct pH, temperature, and time of incubation of the protein emulsion; (c) amount of Molsin used per 100 gms protein (d) rate of drum drying the homogenized protein emulsion at 40 psig. The yield of the CRP per kg. mung grits processed was calculated to be 348 gm. The CRP recovery was 90% based on weight of protein used. With the suggested method of protein extraction, it can be assumed that the starch will absorb the primary cost of the mung grits as raw material and the protein recovered will be at salvage value which covers the cost of Na3PO4 and HCl used in extraction and precipitation of the protein. This will redound to a calculated material cost of CRP of about P4.77/kg (Appendix K). The commercial production of CRP would be feasible if the processing of mung bean starch were centralized to meet the needs of the sotanghon and other industries.